Improving process reliability by means of detection of weld seam irregularities in copper via thermographic process monitoring - Schaumberger, Kerstin; Beck, M.; Saffer, Judith; Kaufmann, Florian; Ermer, J.; Roth, S.; Schmidt, Michael (Procedia Manufacturing, 2019)
Laser beam welding plays an important role in automotive industry as it offers a number of advantages. These include contactless joining, localized energy input, thermally and mechanically durable welds and low electrical contact resistance of the bonded connections. The latter is exploited in the laser beam welding of copper contacts as used for electrical connections in e-mobility. However, copper entails a higher susceptibility to seam defects due to the metallurgical properties compared to, for example, car body materials which in many cases are processed by laser beam as well. In order to meet the high standards of the automotive industry an inline validation of the connections is essential. A suitable method is the monitoring of the welding process by means of thermography which has already proven itself for other metals and joining techniques but has not yet been investigated in detail for laser beam welding of copper. Consequently, this paper deals with the possibilities of thermographic process monitoring in laser beam welding of copper components. It examines the extent to which defects can be registered; so far pores have been detected reliably up to a minimal diameter of 0.5 mm.
CRIS-Team Scopus Importer:2019-10-01
Keywords: Copper; Defects; Infrared thermography; Inline monitoring; Laser beam welding

Light harvesting enhancement upon incorporating alloy structured CdSeXTe1−X quantum dots in DPP:PC61BM bulk heterojunction solar cells - Soltani, Rezvan; Katbab, Ali Asghar; Schaumberger, Kerstin; Gasparini, Nicola; Brabec, Christoph; Rechberger, Stefanie; Spiecker, Erdmann; Alabau, Antoni Gimeno; Ruland, Andres; Saha, Avishek; Guldi, Dirk Michael; Sgobba, Vito; et al. (Journal of Materials Chemistry C, 2017)
Hybrid solar cells based on the pDPP5T-2 electron donating polymer, [6,6]-phenyl-C-butyric acid methyl ester (PCBM) and cadmium selenide telluride (CdSeTe) quantum dots (QDs) are fabricated and their photovoltaic performance and optoelectronic properties are investigated as a function of QD loading. The power conversion efficiency (PCE) of hybrid solar cells is improved up to 5.11% for the device containing 4 wt% of QDs which is mainly due to the enhancement in short circuit current density (J) resulting from increased light harvesting. A full-fledged study is performed on the microstructure, charge transfer/transport and recombination mechanisms of our ternary hybrid solar cells by employing various advanced techniques. The transmission electron microscopy (TEM) results reveal the non-agglomerated and uniform distribution of the CdSeTe QDs within the pDPP5T-2:PCBM host matrix at low QD concentrations. Transient absorption spectroscopy (TAS) showed a slower charge carrier recombination rate due to the introduction of QDs into the photoactive layer. It can be attributed to the more efficient exciton dissociation in ternary systems. These findings are consistent with the photovoltaic properties of the device.
Keywords: Engineering controlled terms: Absorption spectroscopy; Butyric acid; Cadmium compounds; Cadmium telluride; Charge transfer; Heterojunctions; High resolution transmission electron microscopy; Nanocrystals; Polymer solar cells; Semiconductor quantum dots; Solar power generation; Transmission electron microscopy Bulk heterojunction solar cells; Charge carrier recombination; Light harvesting enhancement; Optoelectronic properties; Photovoltaic performance; Power conversion efficiencies; Recombination mechanisms; Transient absorption spectroscopies Engineering main heading: Solar cells

Qualification of Direct Diode Lasers for Laser Beam Welding in Order to Enhance Process Efficiency - Schaumberger, Kerstin; Moedl, Michael; Mann, Vincent; Roth, Stephan; Schmidt, Michael (Applied Mechanics and Materials, 2018)
Laser beam welding has become an established joining technique in automotive manufacturing. Common solid-state lasers generate high-quality joints, but they provide low energy efficiency. By contrast, direct diode lasers (DDL) have superior energy efficiency, are cheaper to purchase and additionally require less utility space. To examine the overall performance of direct diode lasers in comparison to disk lasers, welding quality and energy consumption of the two lasers have to be evaluated. Additionally, for this contribution the stability of the DDL’s beam, like temporal variation of focus position and beam shape, is examined. It is found that a focus shift takes place for longer periods of emission, but the variation of the focus diameter in the initial focal plane is negligible. As expected, the direct diode laser consumes less energy than the disk laser for the same output power. Welding experiments are conducted using four different steel alloys that are exemplary for engineering materials used in automotive manufacturing. Metallographic analysis shows that weld seam depths and widths are on average larger using the disk laser. However even with the need for higher output powers to achieve equal seam geometries the DDL consumes less energy and thereby causes less costs. <br
Keywords: Automotive; Cost Saving; Direct Diode Laser; Energy Consumption; Laser Beam Welding